Solve by the substitution method :-
![\frac{3x}{2} - \frac{5y}{3} = - 2 \\ \frac{x}{3} + \frac{y}{2} = \frac{13}{6} \frac{3x}{2} - \frac{5y}{3} = - 2 \\ \frac{x}{3} + \frac{y}{2} = \frac{13}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B3x%7D%7B2%7D++-++%5Cfrac%7B5y%7D%7B3%7D++%3D++-+2+%5C%5C++%5Cfrac%7Bx%7D%7B3%7D++%2B++%5Cfrac%7By%7D%7B2%7D++%3D++%5Cfrac%7B13%7D%7B6%7D+)
Answers
3x/2 - 5y/3 = -2 ⠀⠀⠀⠀ x/3 + y/2 = 13/6
9x - 10y/6 = -2 ⠀⠀⠀⠀2x + 3y/6 = 13/6
9x - 10y = -12 _(i) ⠀⠀ 2x + 3y = 13 _(ii)
- Multiply the equation (i) by 3 & (ii) by 10
3(9x - 10y) = 3(-12)⠀⠀10(2x + 3y) = 10(13)⠀
27x - 30y = -36⠀⠀⠀⠀20x + 30y = 130
- Add both
27x - 30y + 20x + 30y = -36 + 130
27x + 20x = -94
47x = -94
x = -2
- Put x = -2 in (ii)
2x + 3y = 13
2(-2) + 3y = 13
-4 + 3y = 13
3y = 13 - 4
3y = 9
y = 9/3
y = 3
Step-by-step explanation:
3x/2 - 5y/3 = -2 ⠀⠀⠀⠀ x/3 + y/2 = 13/6
9x - 10y/6 = -2 ⠀⠀⠀⠀2x + 3y/6 = 13/6
9x - 10y = -12 _(i) ⠀⠀ 2x + 3y = 13 _(ii)
Multiply the equation (i) by 3 & (ii) by 10
3(9x - 10y) = 3(-12)⠀⠀10(2x + 3y) = 10(13)⠀
27x - 30y = -36⠀⠀⠀⠀20x + 30y = 130
Add both
27x - 30y + 20x + 30y = -36 + 130
27x + 20x = -94
47x = -94
x = -2
Put x = -2 in (ii)
2x + 3y = 13
2(-2) + 3y = 13
-4 + 3y = 13
3y = 13 - 4
3y = 9
y = 9/3
y = 3
hope it helps you